Corporate Social Responsibility: a proposal for its assessment in Cuban hotel facilities - Yusmelys Ferrales-Arias; Amílcar Roldán-Ruenes; Ana de-Dios-Martínez (Anuario Facultad de Ciencias Económicas y Empresariales, 2017)
The present article, after addressing the fundamental elements that characterize the corporate social responsibility approach, proposes a procedure for its evaluation in Cuban hotel facilities through the use of instruments based on indicators developed for this purpose. The study focuses on measuring the degree of social responsibility and the level of responsible performance that allows the installation management to properly align the practices of social responsibility with the installation strategy.